2003
DOI: 10.1080/00016480310000958
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Agnosia in Children after Herpes Encephalitis

Abstract: Four pediatric patients whose bilateral auditory cortices were damaged by herpes encephalitis at an early age were studied. Their brain CT and MRI scans demonstrated common bilateral lesions of the auditory cortices. Their auditory perception was investigated by means of behavioral and objective hearing tests and auditory perception tests. All four patients showed mild or moderate hearing loss in the behavioral hearing test and normal auditory brainstem responses but did not manifest total deafness. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 3 publications
0
5
0
6
Order By: Relevance
“…As with that case, our additional tests confirmed that B-ATOT2 has intact hearing and recognition of sounds other than voices. Hence, she does not have a general auditory agnosia, a potential consequence of childhood herpes simplex encephalitis (Kaga et al 2000(Kaga et al , 2003. Rather, her phonagnosia is a selective auditory agnosia, just as her apperceptive prosopagnosia is a selective visual agnosia.…”
Section: Discussionmentioning
confidence: 98%
“…As with that case, our additional tests confirmed that B-ATOT2 has intact hearing and recognition of sounds other than voices. Hence, she does not have a general auditory agnosia, a potential consequence of childhood herpes simplex encephalitis (Kaga et al 2000(Kaga et al , 2003. Rather, her phonagnosia is a selective auditory agnosia, just as her apperceptive prosopagnosia is a selective visual agnosia.…”
Section: Discussionmentioning
confidence: 98%
“…Hearing loss following neonatal infection can be bilateral or unilateral severe to profound SNHL ( Westerberg et al., 2008 ). One case series described four children with mild to moderate SNHL on ABRs but severe auditory agnosia and bilateral auditory cortex lesions on MRI after herpes encephalitis ( Kaga, Kaga, Tamai, & Shindo, 2003 ).…”
Section: Viruses Causing Congenital and Acquired Hearing Lossmentioning
confidence: 99%
“…Kaga et al (19) berichteten über vier Kinder, deren bilaterale auditorische Kortizes im frühen Kindesalter durch eine Herpes-Enzephalitis geschädigt worden waren. Neben einem geringen Hörverlust (keine Taubheit) fand sich ein Verlust fast aller auditiver perzeptiver Fähigkeiten bei allen vier Kindern, die mittlerweile in spezialisierten Schulen für behinderte bzw.…”
Section: Andere Erkrankungen Des Znsunclassified